(untitled) (Agricultural Engineering, 2022)
Food loss and waste are one of the main problems of global civilization that stir great emotions, especially among the inhabitants of affluent countries of the northern-hemisphere. All actors at the various stages of the food chain, from producers and processors to retailers and final consumers, influence this phenomenon. To combat this problem, many hours and energies are spent both by those involved in grassroots social initiatives and by national and international institutions. Any entity aware of the magnitude of the food waste problem (entrepreneur, citizen, NGO, etc.) entitled to take advantage of concessions, incentives and exemptions from public tributes is a more effective ally in the fight against this scourge of the 21st century than an economic participant constantly punished and sanctioned, and consequently expending most of its energy on tax optimization.